Exploring Mismatched Na+ and Li+ Electrolytes for Li4Ti5O12 Spinel Anodes in Li‐Ion and Na‐Ion Batteries - Thi Hang Vu; Lam Nguyen Phan; Xu‐Feng Luo; Avi Arya; Thao Nguyen; Jeng‐Kuei Chang; Yu‐Sheng Su (Small Structures, 2025)
Li4Ti5O12 (LTO) is a highly promising anode material for both Li‐ion and Na‐ion batteries due to its remarkable structural stability, minimal volumetric expansion, and high safety. Despite extensive research on LTO performance in conventional systems, little attention has been given to its behavior in mismatched electrolyte environments. This study explores the electrochemical behavior of LTO anodes in Na+‐containing electrolytes for Li+/Na+ intercalation, providing new insights into ion intercalation mechanisms and enhancing battery performance. Using different counter electrode and electrolyte configurations, it is revealed that LTO exhibits superior capacity and cycle stability in a mismatched Li/Na+ environment compared to the standard Li/Li+ system, delivering capacities of up to 219 mAh g−1. Electrochemical and structural analyses indicate that enhanced performance stems from the unique interaction between Li+/Na+ and LTO structure, leading to improved charge–discharge performance. Additionally, the Na/Li+ configuration displays unique behavior, where a distinct plateau splitting emerges after the first cycle, indicating complex ion interactions that ultimately affect cycling stability. These findings not only highlight the potential of LTO anodes in mismatched electrolyte systems but also offer a pathway toward more cost‐effective and sustainable energy storage solutions by leveraging sodium–ion electrolytes in place of traditional lithium‐based systems.